Numerical simulation of 3D unsteady flow in roto-jet pump by dynamic mesh technique. (2015) - Huang, Si; Su, Xianghui; Yang, Fuxiang; Guo, Jing
By using 3D dynamic mesh technique, the numerical simulation of the unsteady flow field in a roto-jet pump was performed in this work. All the computational domains, as stationary, were set in the same reference frame. The surface motions of the computational domains were defined by the profile file in FLUENT commercial code, in which the rotational direction and speed of the rotors were specified. Spring-based smoothing, dynamic layering and local remeshing were used to achieve mesh deformation and remeshing. The unsteady solutions of flow field and pressure distribution were solved. After a startup stage, the flow parameters start to exhibit time-periodic behaviour corresponding to blade passing frequency of impeller. The pulsation amplitudes of the radial force acting on the rotor surface are quite considerable.